The open gym—an active (lunch)time offering at all-day schools - Ferrari, Ilaria; Schuler, Patricia; Kress, Johanna; Bretz, Kathrin; Niederberger, Lukas (Frontiers in Sports and Active Living, 2025)
IntroductionThe implementation of “all-day schools” (schools with extended educational programmes) provides pupils with the opportunity to engage in a multitude of different activities and learning contexts throughout the day, in addition to their core, compulsory curriculum. These activities may include a diverse range of sports-oriented activities at regular intervals throughout the school day and are accessible to all pupils, irrespective of gender and socio-cultural background. In the context of the project, “Sport in the School Environment” various extended physical activity programmes were implemented and evaluated in 14 primary all-day schools in Zurich (Switzerland) between 2019 and 2021. This article focuses on the extended pedagogical physical activity of the “open gym,” a free physical activity programme during the lunch break in all-day schools and examines how the open gym is utilised by different groups of pupils in relation to gender and socio-cultural background.MethodsData from 401 s-grade pupils were collected using a standardised questionnaire. The participation of pupils in the different programmes was analysed using descriptive statistics, and the relation between the programmes and the socio-cultural background of the pupils was determined by a chi-square test for nonparametric data.ResultsOverall, 30%–40% of the children participated in different extended educational programmes, with boys participating more frequently than girls. The various activities however, also engaged girls and increased their participation. The initial findings indicate that the pupils made active use of the open gym, with a higher frequency of attendance among boys compared to girls.DiscussionThe results indicate that the open gym is a significantly utilised programme (37% of children participated) and is frequently accessed especially by boys from a variety of different socio-cultural backgrounds.